Analysis Of The Knowledge Level Of Posyandu Cadres In Using The Anthropometric Measurement Kit To Prevent Stunting Risks In The Working Area Of Wonokromo Community Health Center - Sulenti Widiastuti; Nurul Abidah; Mustalia; Noventi, iis; Siti Nur Hasina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
The level of knowledge of Posyandu cadres in assessing stunting includes anthropometric measurements kit such as height (TB) and weight (BB). The anthropometric kit is one of the key components in assessing nutritional status in children and adults. Assessing the nutritional status of infants to predict long-term health complications requires anthropometric kit examinations nutritional status. This study aims to determine the level of most of them are skilled and knowledge is mostly inadequate of Posyandu cadres in anthropometric kit measurements to prevent stunting in the working area of Wonokromo Community Health Center, Surabaya. The method used is descriptive survey, with a sample of 30 Posyandu cadres involved in anthropometric kit measurements. The results of the study show that before training, most Posyandu cadres were not skilled, but after training, most became skilled. The majority of cadres showed inadequate knowledge prior to training before training but improved significantly afterward. It is recommended for health centers to provide repeated training and evaluate Posyandu cadres by imparting knowledge and skills on proper measurement techniques, especially for stunted children, and accompany them during anthropometric kit measurements to ensure better understanding.